GMO Standards, Endogenous Policy and the Market for Information - Mauro Vigani; Alessandro Olper (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
The paper develops a composite index of GMO standards restrictiveness for 60 countries, assigning objective scores to six different regulatory dimensions. Using this index and its components, we empirically investigate the political and economic detfirminants of GMO regulations. Results show that many of the detfirminants highlighted in the theoretical literature, such as the country trade position, the potential gains from GMO adoption, and the consumer risk aversion, are important detfirminants of the restrictiveness in GMO regulations. As a key result there emerges a prominent role for the market of infirmation, showing that the structure of domestic mass media (public vs. private) is an important driver of GMO standards.
Keywords: D72; Q13; Q16; Q18; 330; GMO standards; political economics; media market